THE DESIGN OF EXPLORATORY APPLICATION AND PREPROCESSING OF EVENT LOG DATA IN LMS MOODLE-BASED ONLINE LEARNING ACTIVITIES FOR PROCESS MINING - Aulia, Demaspira; Waspada, Indra (Universitas Muhammadiyah Surakarta, 2019)
Process Mining is one of the sub-studies of Data Mining that focuses on the events of a system. An area that benefits from process mining is education, especially online learning. This study used Moodle as a platform to provide online event activity log data in online learning. Moodle-based process mining requires several stages that are not easily understood directly by teachers. As a solution, some efforts are needed to integrate Moodle with process mining. This study built an application that could contribute to the Preprocessing and Exploratory Data Analysis (EDA) stages of Moodle event log data ? as an important part of the process mining stage. Preprocessing was implemented by using the simple heuristic filtering method, while EDA was employed through visualization using flow control and dotted charts. Eventually, the application built in this study successfully performed preprocessing in Moodle event log data and could display the results visually, as a tool of control flow analysis and dotted chart analysis.